Treatment of experimental amyloidosis with antirheumatic drugs - LEONAVIČIENĖ, Laima; POVILĖNAITĖ, Danutė; BRADŪNAITĖ, Rūta; VAITKIENĖ, Dalia; VENALIS, Algirdas (Acta medica Lituanica, 2010)
Background. Because at present there is no known specific effective therapy for secondary amyloidosis, the aim of this study was to determine whether antirheumatic drugs inhibit the development of experimental AA amyloidosis induced in C57BL/6 mice by casein and fibrin injections.Materials and methods. Monotherapy with sulfasalazine (SSL) and diclofenac (D) and a combined treatment with diclofenac and prednisolone (D/P) according to prophylactic and therapeutic treatment protocols were investigated. The drugs were administered through intragastric gavage 5 times a week for 5 or 4 weeks in the following doses: D – 1 mg/kg, P – 10 mg/kg, and SSL – 100 mg/kg. A histopathological examination of splenic, kidney and hepatic tissues of mice was performed. The amount of amyloid was assessed semi-quantitatively by polarizing microscopy after Congo red staining.Results. Our study indicated that no positive effect of the prophylactic treatment with D could be seen on amyloid deposition in the target organs. Prophylactic combined treatment with D/P resulted in a significant improvement of disease symptoms and markedly reduced amyloid deposits in the spleen, kidneys and liver (p < 0.02–0.001). SSL therapy alone was more successful in the prophylactic treatment of experimental amyloidosis: the decrease of amyloid deposits was statistically significant in all examined organs (p < 0.04–0.001), and the suppression of amyloid formation was most significant in the kidneys and liver (p < 0.004–0.001). In the therapeutic treatment of experimental amyloidosis, combined treatment with D/P showed the most pronounced inhibition of amyloid formation in the internal organs (p < 0.006–0.001). The suppression (by 86.7%; p < 0.001) of amyloid deposits was most notable in the liver. Treatment of mice with D alone produced a significant reduction in amyloid deposition only in the liver (p < 0.03) and with SSL only in the spleen (p < 0.03).Conclusions. These findings suggest that D/P and SSL at relevant doses suppress amyloidogenesis, and this suppression is possibly related to the anti-inflammatory effect of antirheumatic drugs. Although these drugs cannot completely inhibit the disease in this model, a possibility remains that they may be clinically useful in rheumatic diseases associated with the formation of amyloidogenic derivatives.Keywords: mice, experimental AA amyloidosis, antirheumatic drugs